Sistem Penyiraman IoT Bagi Pekebun Kecil - Mohd Abbas, Mohamad Adli; Ismail, Amir; Fikri, Danial; MA'RADZI, AHMAD ALABQAR (Multidisciplinary Applied Research and Innovation, 2022)
Irrigation or watering system is a vital step when you want to maintain the quality and the quantity of the plants. This is because most of the plants in the world need high level of soil moisture to grow bigger and healthier. Unfortunately, we are living in a busy world plus the pandemic are making the gardeners and farmers lose their jobs at the moment. A wireless system which capable of perceiving the proper situation of watering plants in needed in this situation. In this report, a microcontroller NodeMCU and some sensors such as rain sensor and soil moisture sensor are used in making an efficient machine that controls the watering system. Moreover, it is connected to an application called Blynk that can present the information about the surrounding of the plants plus controlling the water pump for watering the plant.